Supplementum 272: Abstracts of the Annual meeting of the Swiss Society of Gastroenterology, the Swiss Society of Visceral Surgery, the Swiss Association for the Study of the Liver and the Swiss Society of Endoscopy Nurses and Associates (Interlaken, Switzerland, September 14−15, 2023) (Swiss Medical Weekly, 2023)
No abstract available.